Proceedings of the Thirteenth Conference on Computational Natural Language Learning Shared Task - CoNLL '09 2009
DOI: 10.3115/1596409.1596416
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual semantic role labeling

Abstract: This paper describes our contribution to the semantic role labeling task (SRL-only) of the CoNLL-2009 shared task in the closed challenge (Hajič et al., 2009). Our system consists of a pipeline of independent, local classifiers that identify the predicate sense, the arguments of the predicates, and the argument labels. Using these local models, we carried out a beam search to generate a pool of candidates. We then reranked the candidates using a joint learning approach that combines the local models and propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
156
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 7 publications
1
156
0
2
Order By: Relevance
“…Previous related approaches to semantic role labeling include joint classification of semantic arguments (Toutanova et al, 2005;Johansson and Nugues, 2008), latent syntax induction (Boxwell et al, 2011;Naradowsky et al, 2012), and feature engineering for SRL (Zhao et al, 2009;Björkelund et al, 2009). Toutanova et al (2005) introduced one of the first joint approaches for SRL and demonstrated that a model that scores the full predicateargument structure of a parse tree could lead to significant error reduction over independent classifiers for each predicate-argument relation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous related approaches to semantic role labeling include joint classification of semantic arguments (Toutanova et al, 2005;Johansson and Nugues, 2008), latent syntax induction (Boxwell et al, 2011;Naradowsky et al, 2012), and feature engineering for SRL (Zhao et al, 2009;Björkelund et al, 2009). Toutanova et al (2005) introduced one of the first joint approaches for SRL and demonstrated that a model that scores the full predicateargument structure of a parse tree could lead to significant error reduction over independent classifiers for each predicate-argument relation.…”
Section: Related Workmentioning
confidence: 99%
“…Models for SRL have increasingly come to rely on an array of NLP tools (e.g., parsers, lemmatizers) in order to obtain state-of-the-art results (Björkelund et al, 2009;Zhao et al, 2009). Each tool is typically trained on hand-annotated data, thus placing SRL at the end of a very highresource NLP pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…We basically use the feature set proposed by Björkelund et al (2009). During the prediction, there are some predicates which have not been seen in the training data.…”
Section: Srl Task Descriptionmentioning
confidence: 99%
“…This type of framework has the ability to use SRL information in syntactic parsing for improvement, but needs a much larger search space for decoding. The other type is called SRLonly task (Zhao et al, 2009;Björkelund et al, 2009), which uses automatic morphological and syntactic information as the input in order to judge which token plays what kind of semantic role. Our work focuses on the second category of SRL.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation